Rapid preparation of decellularized trachea as a 3D scaffold for organ engineering. Issue 1 (January 2021) - Wang, Zhihao; Sun, Fei; Lu, Yi; Pan, Shu; Yang, Wenlong; Zhang, Guozhong; Ma, Jun; Shi, Hongcan
Objective: To shorten the preparation time of rabbit decellularized tracheal matrix through a modified detergent-enzymatic method with higher concentration of DNase (50 kU/mL), providing an experimental and theoretical basis for clinical decellularization technology. Methods: The control group was a natural trachea, and the experimental group was a tracheal matrix subjected to two and four decellularization cycles. The performance of each group of samples was evaluated by histology and immunohistochemical staining, scanning electron microscopy, biomechanical property testing, inoculation and cytotoxicity tests, and allograft experiments. Results: The results showed that the nuclei of the nonchondral areas of the tracheal stroma were essentially completely removed and MHC-I and MHC-II antigens were removed after two decellularization cycles. Histological staining and scanning electron microscopy showed that the extracellular matrix was retained and the basement membrane was intact. Cell inoculation and proliferation tests confirmed that the acellular tracheal matrix had good biocompatibility, and the proliferation capacity of bone mesenchymal stem cells on the matrix was increased in the experimental group compared with the control group ( p  < 0.05). Histological staining and CD68 molecular marker analysis after the allograft experiment showed that the inflammatory response of the acellular tracheal matrix was weak and the infiltration of surrounding macrophages was reduced. Conclusion: A modified detergent-enzymatic method with an increased DNase (50 kU/mL) concentration requires only two cycles (4 days) to obtain a decellularized rabbit tracheal matrix with a short preparation time, good biocompatibility, suitable mechanical properties, and reduced preparation cost.